Technological decision modelling of the dwelling house walls insulation/Gyvenamųjų namų sienų šiltinimo technologinių sprendimų modeliavimas - Juodis, Arvydas; Janušaitis, Rolandas (Journal of Civil Engineering and Management, 1998)
The article investigates the problems of technological decision modelling of wall insulation in dwelling houses. The system engineering is the base of that technology. The methodology represents and optimises the systems of complex building processes. After that it is possible to develop the alternatives. On a systematic engineering methodological basis, there was created a technological network model of the decisions of wall insulation. This model has been constructed on the base of classical net model with a new modification for application provided. The main stages of technological network model of wall insulation are: – formation of complex combination process; – establishment of possible variants of the partial process; –technological connection among those (b and c) processes. The implementation alternatives of the analysed process have pointed out in the technological net model for the decisions of wall insulation. Such a model enables to analyse, to evaluate and to optimise the decisions of wall insulation. Article in Lithuanian. First Published Online: 26 Jul 2012